2021
DOI: 10.1136/bmjopen-2020-038975
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and associated factors of hypertension in selected urban and rural areas of Dhaka, Bangladesh: findings from SHASTO baseline survey

Abstract: ObjectiveWe implemented this study to report the prevalence and associated risk factors of hypertension among adult men and women aged >30 years residing in selected urban and rural areas of Dhaka division, Bangladesh.DesignCross-sectional study.SettingTwo urban (Dhaka city north and Dhaka city south) and two rural (Narsinghdi and Gazipur district) areas of the Dhaka division.ParticipantsA total of 4856 male and female participants were included in the final analysis, of whom 2340 (48.2%) were from urban an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 45 publications
(41 reference statements)
1
10
0
Order By: Relevance
“…But it is comparable to previous studies carried out in Senegal in Saint Louis in 2011 which had found a prevalence of 46% (33)and that carried out in Guéoul in 2012 of 46.6% (34). In comparison to studies carried out on the subject, outside Senegal, it turned out that this prevalence is higher than the 31% found in Bangladesh in Asia (47 (47) This prevalence of hypertension, close to 50% in this study, is due to a signi cant proportion of self-reported cases of 31.3% whose hypertensive status has been poorly documented. This constitutes a limit in determining the prevalence of the disease.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…But it is comparable to previous studies carried out in Senegal in Saint Louis in 2011 which had found a prevalence of 46% (33)and that carried out in Guéoul in 2012 of 46.6% (34). In comparison to studies carried out on the subject, outside Senegal, it turned out that this prevalence is higher than the 31% found in Bangladesh in Asia (47 (47) This prevalence of hypertension, close to 50% in this study, is due to a signi cant proportion of self-reported cases of 31.3% whose hypertensive status has been poorly documented. This constitutes a limit in determining the prevalence of the disease.…”
Section: Discussionsupporting
confidence: 84%
“…, 19.5% in Ethiopia in 2016(47), to 30.3% in Uganda and 2015 (48), to 38.9% in South Africa in 2016(49). It should be noted in Cameroon the study by Dzudie, A et al had similar results with a prevalence of 47.5%(50) …”
mentioning
confidence: 73%
“…Results of the current study are supported by several studies from LMICs suggesting individuals from the affluent communities at an increased risk of hypertension compared to those from resource poor settings [ 52 , 55 57 ]. Based on the Popkin’s framework [ 58 ], like other LMICs, Nepal could be in the later stage of the nutritional and epidemiological transition characterized by increased accessibility and affordability of fats and refined food, increased intake of sugars and salts, sedentary behaviors, and higher prevalence of overweight and obesity [ 43 , 55 , 59 61 ]. These characteristics are particularly common in the affluent societies in LMICs [ 62 , 63 ].…”
Section: Discussionmentioning
confidence: 99%
“…The Bangladesh Bureau of Statistics (BBS) reported that more than 18 lakh people, or almost 20% of the total population, reside in slums ( 20 ). Over 8.84 million people call the slums of Dhaka Division their home.…”
Section: Introductionmentioning
confidence: 99%
“…Over 8.84 million people call the slums of Dhaka Division their home. On the other hand, a total of 40 lakhs ( 20 , 21 ) is the estimate provided by several non-governmental groups. The appalling living conditions in the slums pose serious threats to the physical and mental health of the majority of the inhabitants.…”
Section: Introductionmentioning
confidence: 99%